Toisto-metodi: vastasaapuneiden ukrainalaisten kokemuksia suomen oppimisesta Toisto-tuokioissa - Hanna-Ilona Härmävaara; Topi Levänen; Olga Nenonen (Lähivõrdlusi)
Tässä tutkimuksessa tarkastellaan Suomeen vastasaapuneiden ukrainalaisten kokemuksia suomen kielen oppimisesta Toisto-tuokioissa. Keräsimme tapaustutkimuksemme aineiston havainnoimalla kahden Toisto-ryhmän toimintaa 10 kuukauden ajan. Toimintaa koskevien muistiinpanojen lisäksi aineistomme koostuu Toisto-tuokioiden videotallenteista sekä osallistujien haastatteluista. Haastattelujen temaattinen analyysi paljasti Toisto-tuokioihin osallistuneiden kokeneen metodin miellyttäväksi ja ilmapiirin hyväksi. Osallistujat kokivat oppineensa hyödyllisiä fraaseja, ja hyväksi koettiin myös puhumisen ja ääntämisen harjoittelu sekä itse toistoon perustuva metodi. Haastavaksi taas koettiin kirjoitetun materiaalin niukkuus sekä se, ettei kielen rakenteita selitetä. Sekä haastattelu- että videoaineistosta ilmeni osallistujien tarve ymmärtää kielen rakenteita syvemmin kuin mihin analysoimattomien konstruktioiden esittelyyn tähtäävä metodi tarjoaa mahdollisuuden. Osallistujat kysyivät itselleen epäselvistä asioista paitsi oppailta myös toisiltaan. Oppailta kysymistä helpottivat oppaiden ja osallistujien yhteiset kielet venäjä ja englanti. "The Toisto-method: Language learning experiences of newly arrived Ukrainians in Finland." This study focuses on how newly arrived Ukrainian refugees to Finland have experienced learning Finnish language with a method called Toisto (’Repetition’). Toisto is a modeling-based method that was developed to enable volunteers to teach the basics of Finnish to newcomers, as linguistic first aid. The Toisto-method is built on the ideas of direct method, communicative teaching, suggestopedic atmosphere, and authenticity in schemata. The method is speech-based, and one does not have to have literacy skills to participate. The case study was conducted by observing two groups for ten months, by interviewing the participants and by videorecording four sessions. All participants were Ukrainian refugees who had an extensive educational background, including learning other languages. In the interviews, the participants reported that they were happy with the sessions, and they found the atmosphere relaxed. They felt that the Toisto-method was novel compared to their previous language learning experiences both in Ukraine and in Finland. The participants reported that the method helped them learn useful phrases for their everyday needs, and they found that the speech-based method was beneficial especially for developing their communicative skills. The participants also recognized that not all their language learning needs were met in Toisto-sessions. The participants reported also wanting to learn how to write Finnish, and they wished to have explicit grammar instruction. Both writing and explicit teaching of grammar are excluded from the method on purpose, and based on the analysis, the expectations of the Ukrainian participants were often different from what the method is set to offer. To better cater for the needs of the participants, the Finnish volunteers had added written modality in the lessons, and they also explained linguistic details when asked. The analysis of the language related questions in Toisto-sessions revealed that instead of focusing on inferring the meanings and structures from the presented materials, the participants asked for translations to Russian and made questions about grammar. These practices had brought the Toisto-sessions closer to more traditional language learning.